Development of Nutraceutical and Nutritional Design Method for Liposomal Curcumin and Vitamin C Using Microstructural and Elemental Analysis - Yakup Ermurat (Kemija u Industriji)
The biomolecular components of curcumin are potent inhibiting nutraceuticals with hydrophobic characteristics. Vitamin C, a water-soluble antioxidant, plays a crucial role in strengthening the body’s immune system. Liposomal encapsulation enhances the solubility and bioactivity of curcumin, while also increasing the bioavailability of vitamin C. In this study, a functional nutraceutical and nutritional design method was developed using structural and elemental analysis of prepared liposomal curcumin and liposomal curcumin-vitamin C nanoparticles, utilising scanning electron microscopy. The microstructural images of the liposomal curcumin nanoparticles revealed their hydrophobic nature and adequate structural model. The liposomal curcumin-vitamin C displayed solid surface spherical particles in their dried forms. The peak patterns graph and data of the elemental constituents of the liposomal curcumin samples indicated high levels of carbon and oxygen, while the liposomal curcumin-vitamin C samples showed elemental carbon and oxygen, as well as minerals Mg, P, and K.